0788 Periodic Limb Movements in Sleep in Pediatric Headache Patients. (27th April 2018) - Kovacs, R; Garraway, D; Weiss, M; Lew, J
Abstract: Introduction: Approximately 70–80% of the patients with restless leg syndrome (RLS) have periodic limb movements during sleep (PLMS). Previous studies have shown a high prevalence of RLS in patients who experience frequent headaches. These results were replicated in a recent pediatric sample, showing a high frequency of RLS in pediatric headache patients. The prevalence rate of PLMS in normal children is about 7.7%. Given that children have difficulty describing their RLS symptoms, we were interested in assessing the prevalence of periodic limb movement index (PLMI) in children who have experienced headaches and have undergone sleep studies for clinical purposes. Methods: The current study is a retrospective chart review. Children between the ages of 2 to 18 years with a history of headaches, who underwent a sleep study from January 2007 to December 2015 were included in the study. Subjects with a periodic limb movement index (PLMI) ≥ 5/h in sleep were included in the periodic limb movement in sleep (PLMS) group. Results: In total, there were 86 patient records that were included in data analysis. Out of those, 39 (45.3%) were male. Average age of participants was 11.9 years. When analyzing PLMS prevalence, there were only 7 (8.10%) patients who meet the PLMS diagnosis criteria. Since the sample size for the PLMS group was small, no parametric statistics were run between the PLMS and non-PLMS group. There was a notable difference in decreased total sleep time in the PLMS group. Children in the PLMS group also had decreased stage 3 sleep time percentage, shortened sleep onset latency and decreased NREM sleep time percentage. Conclusion: We found slightly higher periodic limb movements in sleep in the pediatric headache patients than in the age-comparable normal children noted in the literature. Given previous findings of restless leg syndrome in the headache patient population, more research is needed in this area. Clinical assessment of restless leg symptoms and polysomnographic evaluation for periodic limb movements may need to be considered in the clinical evaluation and management of this group of patients. Support (If Any): n/a